Safety of a low-fat fermented sausage produced with Enterococcus faecium CRL 183 and Lactobacillus acidophilus CRL1014 probiotic strains - Roselino, M. N. [UNESP]; Almeida, J. F. de [UNESP]; Canaan, J. M. M. [UNESP]; Pinto, R. A. [UNESP]; Ract, J. N. R.; Paula, A. V. de [UNESP]; Valdez, G. F. de; Rossi, E. A. [UNESP]; Cavallini, D. C. U. [UNESP] (Univ Putra Malaysia Press, 2017)
This work is aimed at studying the effect of using lactic acid bacteria with lipid-lowering properties (Enterococcus faecium CRL183 and Lactobacillus acidophilus CRL1014) on the physicochemical characteristics and safety of fermented sausages with fat and curing salt reduction. The probiotic cultures were submitted to preliminary tests for evaluating their resistance to curing salts and their capacity to produce antimicrobial substances. The sausage quality was evaluated by analyses at the beginning of the processing and during the ripening and storage periods. The E. faecium CRL 183 exhibited no log reduction in the population of viable cells (10(9) CFU mL) while the L. acidophilus CRL 1014 showed a reduction in comparison with the control treatment (10(8) CFU/mL). All formulations presented appropriate physicochemical and microbiological characteristics to the standards established. The formulations F2-F7 (with fat reduction) showed an increase in oleic acid and decrease in saturated acid content, compared to control sausage. The microbiological safety and technological properties it was not compromise. (c) All Rights Reserved
Keywords: Bacteriocins; Microbiological safety; Olive oil; Sodium nitrite; Meat products